Mineral Heterogeneity Characterization of the Lacustrine Yanchang Shales, Ordos Basin Using Micro-Fourier Transform Infrared Spectroscopy (Micro-FTIR) Technique. (29th August 2021) - Luo, Bing; Shu, Zhiguo; Chen, Yalin; Li, Zhuo; Hou, Yufei; Wang, Liwei; Yang, Youdong; Liang, Zhikai
Abstract : Shale is a typical fine-grained sedimentary rock with small grain sizes of matrix components, significant lithofacies variation of rock texture and structure, and strong heterogeneity of organic matter and mineral compositions. Characterization of mineral compositions and their heterogeneity in micro- to nanoscale are the key parameters to gas shale pore structure and rock physical properties. In order to study the microscale mineralogy heterogeneity of the lacustrine shales in the Triassic Yanchang Formation in the Ordos Basin, the micro-Fourier transform infrared spectroscopy (micro-FTIR) technique was conducted. Based on the specific micro-FTIR spectra peaks, the abundance of mineral compositions can be quantitatively determined in the selected microscale areas. The results show that within the range of 80  μ m micro-FTIR test interval, both massive argillaceous shale and silty interlayered shale show obvious heterogeneity; in particular, the relatively homogeneous shale observed by the naked eyes also has strong mineral heterogeneity. The results of micro-FTIR spectra are basically consistent with the bulk X-ray diffraction (XRD) data. The advantage of this micro-FTIR technique includes higher resolution (less than 100  μ m) and in situ mineral characterization of shale samples at micro- and nanoscale.